Monitoring lateral and longitudinal displacements in structures using single and multiple metamaterial sensing techniques - Ang, Jason (2018)
All Civil infrastructures are constructed with a long-term service life. However, it is not known durability and length of every structure during it’s service life. People start to panic even when there is a slight vibration or a crack. This implies a large importance to Structural Health Monitoring (SHM). In recent years, the development of SHM has been increasing due to the introduction of Wireless Sensors Network (WSN) enabling large networks to join as a single platform. Due to the challenges procuring from wired sensors, wireless sensors such as metamaterials are now at an increasing trend to solve the issues. While several wired sensors are not sufficiently robust to bending, metamaterials are the next best solution. They need not be surface bonded or embedded in structures. This final year project has illustrated the function of the metamaterial-based sensors of not being surface bonded to structures. These sensors adopt electromagnetic (EM) waves based emit-detect method to capture any possible sensor. This depends on travelling of waves on the engineering structures. This project has also exhibited the ability of a neighbouring piezo sensor as a catchment area to detect the presence of EM waves. The report also incorporated robotic application to illustrate the convenience and efficiency that it can bring to the world of SHM.